2022
DOI: 10.1186/s12978-022-01346-5
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors of first-birth interval among women in reproductive age, addressing maternal and child health

Abstract: Background The first-birth interval directly influences family size and maternal and child mortality. The objective of this study is to investigate factors associated with the time of the first-birth after the first marriage among women in Iran. Methods In this cross-sectional study, the first birth history of 1350 women aged 15–49 years was collected in Kerman (southern Iran) in 2018. To assess the predictor variables of the first-birth interval a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…It implies the implication that the birth intervals of mothers would be different over time. The birth intervals of illiterate mothers were shorter than the birth intervals of educated mothers which are in line with a study reported in Dehesh et al 23 that reported that household education level has positive effects on birth intervals of mothers'.…”
Section: Parameter Estimationsupporting
confidence: 91%
“…It implies the implication that the birth intervals of mothers would be different over time. The birth intervals of illiterate mothers were shorter than the birth intervals of educated mothers which are in line with a study reported in Dehesh et al 23 that reported that household education level has positive effects on birth intervals of mothers'.…”
Section: Parameter Estimationsupporting
confidence: 91%
“…Total fertility rate is the average number of live births a woman would have throughout her reproductive life if she had the present age‐specific fertility rates 20 . In 2019, the total fertility rate in the United States of America (USA) and the European Union (EU) was 1.70 and 1.53 live births per woman, respectively 21…”
Section: Methodsmentioning
confidence: 99%
“…These factors play a very important role in influencing the level of fertility and consequently the size of the population in the community. (Dehesh, Malekmohammadi, & Dehesh, 2022) investigated the factors associated with the time of the first-birth (FBI) in Iran by using multivariate Cox regression. This study concluded that the average of FBI is 2.5 ∓ 0.8 years.…”
Section: Literature Reviewmentioning
confidence: 99%